Pedagogická fakulta Univerzity Palackého v Olomouci - Vitásková, Kateřina (Logopedia Silesiana, 2015)
The objective is the analysis of examinations (evaluated by means of subjective and objective criteria) focused on identifying voice and speech problems experienced by interpreting students as a specific group of vocal professionals in relation to the prevention of voice disorders and voice hygiene. Methodology: Students who are studying interpreting and whose vocal and overall communication expression has been analysed through direct observation and through the analysis of video records have been evaluated by means of a questionnaire focused on identifying voice and speech problems and by means of subjective evaluation of the possible impact of these problems on their profession. The resultant analysis shows, among other things, that vocal professionals experience objective problems in the use of their voices, which are chronic in some cases. Most students have subjectively evaluated their vocal expression as average and as significantly influenced by the psychosomatic factors disrupting their performance in the sphere of executive and cognitive functions and by the dialect. Some of the subjective feelings are strongly related to the possible exhibitions of vocal disorders. In many cases, the analysis of video records has proven non-compliance of the subjective evaluation of the students’ exhibitions with the objective experience and the idea of voice and speech professionalism. The results have served, among other things, for setting other education and enlightenment objectives in the sphere of vocal and speech prevention and for capturing possible deviations, even based on the comparison of this preliminary data with the results of similarly focused examinations implemented by the speech and language therapy department.